2019
DOI: 10.1177/2470289719827306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Bases of Mammalian Maternal Behavior

Abstract: New mammalian mothers undergo an increase in their maternal responsiveness with the birth of their infants. Associated with changes in responsiveness are how attracted mothers are to infant cues, mothers' affective state, and their cognitive and executive function. In comparison to nonmothers, new mothers are more attracted to infant odors and are more easily alerted to their vocalizations; they undergo a reduction in withdrawal behaviors and anxiety, but increased lability. Their maternal sensitivity (human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 172 publications
(283 reference statements)
0
19
0
Order By: Relevance
“…Studies of gene x environment interactions on maternal behavior to date have focused on human cohorts. These studies have identified SNPs in oxytocin‐ and dopamine‐related genes that interact with early‐life experiences on different components of mothering behavior (Fleming & Kraemer, 2019; Jonas et al., 2013; Mileva‐Seitz et al., 2012, 2013; Tombeau Cost et al., 2017) and that can be mediated by executive function (Tombeau Cost et al., 2017) or depressive symptoms (Jonas et al., 2013). A strength of our study is application of statistical models typically used in human cohorts to rat populations, where causal biological mechanisms can be more readily examined (Jenkins et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of gene x environment interactions on maternal behavior to date have focused on human cohorts. These studies have identified SNPs in oxytocin‐ and dopamine‐related genes that interact with early‐life experiences on different components of mothering behavior (Fleming & Kraemer, 2019; Jonas et al., 2013; Mileva‐Seitz et al., 2012, 2013; Tombeau Cost et al., 2017) and that can be mediated by executive function (Tombeau Cost et al., 2017) or depressive symptoms (Jonas et al., 2013). A strength of our study is application of statistical models typically used in human cohorts to rat populations, where causal biological mechanisms can be more readily examined (Jenkins et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Seminal research examining natural variations in maternal care received between litters found that there is also substantial within‐litter variation in later‐life maternal care provisioning (Champagne et al., 2003). In addition, studies with human cohorts in nonclinical populations have shown a modest relationship between parental care received and parental care provisioning (Van Ijzendoorn, 1992) and found that the genotype of the individual can interact with the early‐life environment or directly affect maternal care provisioning (Fleming & Kraemer, 2019). Studies in mice also show an important role of offspring genotype in maternal care received (Ashbrook et al., 2015, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Providing readers with a full discussion of how these genes are involved in biochemical pathways connecting maternal behavior and infants' developmental outcomes is beyond the aims of the present paper. Notwithstanding, it should be highlighted that both genetic variations in the allelic version of these genes have been previously associated with individual differences in maternal caregiving and/or were found to moderate the effect of maternal regulatory behavior on the offspring behavioral, emotional and stress regulation across infancy and childhood . One can speculate that—as far as maternal sensitive caregiving emerged as a key dimension of maternal behavior linked with the offspring regulation of methylation—at least some of these genes may be involved in a pathway that is highly relevant for intergenerational transmissions among mothers and their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of gene x environment interactions on maternal behavior to date have focused on human cohorts. These studies have identified SNPs in oxytocin-and dopamine-related genes that interact with early-life experiences on different components of mothering behavior 16,[40][41][42][43] and that can be mediated by executive function 40 or depressive symptoms 41 . A strength of our study is application of statistical models typically used in human cohorts to rat populations, where causal biological mechanisms can be more readily examined 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Seminal research examining natural variations in maternal care received between litters found that there is also substantial withinlitter variation in later-life maternal care provisioning 14 . In addition, studies with human cohorts in nonclinical populations have shown a modest relationship between parental care received and parental care provisioning 15 and found that the genotype of the individual can interact with the early-life environment or directly affect maternal care provisioning 16 . Studies in mice also show an important role of offspring genotype in maternal care received 17,18 .…”
Section: Introductionmentioning
confidence: 99%